Profile of palliative care by home care service in Divinópolis-MG - Silva, Alexandre Ernesto (2023)
Introduction: Palliative care (PC) is aimed at controlling physical, social, spiritual and emotional symptoms. In Brazil, there is currently a scenario of accumulation of terminally ill patients, which contributes to the country being considered the 3rd worst to die in. Dehospitalization, with patients attended to by a home care service (HCS), is seen as a way to improve patients’ quality of life and reduce costs for the national health system. Objective: To identify the profile of patients in PC assisted by the HCS of Divinópolis-MG, as well as the service’s interventions and their effectiveness. Methods: Descriptive study carried out from the retrospective analysis of medical records of patients who were discharged from the HCS of Divinópolis-MG between 2020-2021, with quantitative collection of the following data: sex, age, home address, responsible multidisciplinary home care team (EMAD), type of illness, interventions of HCS teams, effectiveness of HCS interventions, symptoms presented, effectiveness of symptom control and reason for discharge from the service. Results: Data were collected from 72 medical records, from which, an average age of 67 years was found, with a predominance of female patients and neurodegenerative diseases. Regarding the symptoms presented in the medical records, 54 were treated effectively and 23 ineffectively, and 22 were not treated. Discharges for symptom control accounted for 43% of the total. Conclusion: The HCS's ability to adequately manage patients eligible for PC is highlighted, to control symptoms — physical, social, psychological and family — , contributing to the improvement of the quality of life of the patient and their social circle.